Calibration of two passive air samplers for monitoring phthalates and brominated flame-retardants in indoor air. (October 2015) - Saini, Amandeep; Okeme, Joseph O.; Goosey, Emma; Diamond, Miriam L.
Highlights: SIPs were characterized for estimating indoor air concentrations of phthalates. PUFs were characterized for estimating indoor air concentrations of BFRs. Sampling rates ( R ) reported for predominantly gas-phase phthalates and BFRs. A generic R of 3.5 ± 0.9 m 3 /day is recommended for partially sheltered SIPs and PUFs. We recommend use of partially sheltered housing and one month deployment period. Abstract: Two passive air samplers (PAS), polyurethane foam (PUF) disks and Sorbent Impregnated PUF (SIP) disks, were characterized for uptake of phthalates and brominated flame-retardants (BFRs) indoors using fully and partially sheltered housings. Based on calibration against an active low-volume air sampler for gas- and particle-phase compounds, we recommend generic sampling rates of 3.5 ± 0.9 and 1.0 ± 0.4 m 3 /day for partially and fully sheltered housing, respectively, which applies to gas-phase phthalates and BFRs as well as particle-phase DEHP (the later for the partially sheltered PAS). For phthalates, partially sheltered SIPs are recommended. Further, we recommend the use of partially sheltered PAS indoors and a deployment period of one month. The sampling rate for the partially sheltered PUF and SIP of 3.5 ± 0.9 m 3 /day is indistinguishable from that reported for fully sheltered PAS deployed outdoors, indicating the role of the housing outdoors to minimize the effect of variable wind velocities on chemical uptake, versus the partially sheltered PAS deployed indoors to maximize chemical uptake where air flow rates are low.